Revealing community cultural wealth through counterstories: a narrative analysis of first-generation mujeres in a predominantly white-serving institution - Berumen, Graciela (Kansas State University, 2021)
Utilizing a Critical Race Theory foundation, a Latino Critical Race Theory focus, and a Community Cultural Wealth lens, this assets-based qualitative study examined the counterstories of four first-generation women (mujeres) attending a predominantly white-serving institution in the Midwest. The increasing number of first-generation students pursuing higher education provides an opportunity to assess systems in place for recruiting, retaining, and serving first-generation students. This study presents the need to shift from a deficit perspective when working with first-generation students to an assets-based perspective that centers and values the voices of historically-excluded students, seeing the importance of their experiential knowledge. Interviews and journal entries were used to collect counterstories that focused on the six forms of capital outlined in community cultural wealth: aspirational capital (hopes and dreams), linguistic capital (intellectual and social skills), familial capital (cultural knowledge), social capital (networks of people and community resources), navigational capital (maneuvering through social institutions), and resistant capital (knowledge and skills forged through oppositional behavior). The data collected supported the six priori themes based on the six forms of capital in community cultural wealth, additional themes identified supported the link between representation and validation of historically-excluded populations as a path towards graduation.
Keywords: Critical race theory; First-generation college student; Funds of knowledge; Latino critical race theory; Community cultural wealth